Feminism and the Making of Canadian Working-Class History: Exploring the Past, Present and Future - Sangster, Joan (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2000)
Abstract This paper explores the writing of women's labour history in Canada over the last thirty years. Three interconnected forces have shaped the contours of this intellectual production: the course of feminist, Left, and labour organizing; trends in international social theory; and directions in Canadian historiography. Feminist challenges to the initially 'masculinist' shape of working-class history, along with more recent calls to integrate race and ethnicity as categories of analysis, have produced important shifts in the overall narrative of Canadian working-class history and in the dominant paradigms used to examine labour. As a result, gender has been more effectively, though certainly not completely, integrated into our analysis of class formation. More recent post-structuralist theoretical trends, along with the decline of the Left and labour militancy, have called into question some fundamental suppositions of women's and working-class history, creating an unsettled and uncertain future for a feminist and materialist exposition of class formation in Canada.